EXPLORING POWER AND SOLIDARITY SEMANTIC IN TRANSLATION OF CULTURAL TERMS OF ADDRESS IN THE BIBLE - Frans I Made Brata (Linguistik Indonesia, 2013)
This paper presents the types of meanings in the translation of English Luke’s Bible in Balinese. The Tu-Vous combined with attitude in the Appraisal Theory are utilized to evaluate the word choice of terms of address done by the translator. The results are as follows: (1) Pronouns and nouns employed among characters with different social stratification were related to power semantic. (2) Pronouns and nouns employed among characters in the same social stratification were related to solidarity semantic. (3) The addresser’s attitude, either positive [+], or negative [-] in a communication situation results in meaning shift in translation.